Watch out! Travellers’ valuation of reduced avalanche risks on railways and roads - Knut Veisten; Ståle Navrud; Kristin Magnussen (Transportation Research Interdisciplinary Perspectives)
In various regions of the World, railway and road sections are affected by avalanches. Protective measures can reduce the risk of casualties as well as the risk of infrastructure closures. This paper explores the identification of additional economic benefits from avalanche risk-reducing measures. E.g., it has been hypothesized that avalanche risk provokes insecurity or worry, due to the avalanche risk as such. If there are additional benefit elements, these need to be assessed together with those impacts that are already accounted for, to avoid potential double-counting of benefits.We applied a survey-based discrete choice experiment to a sample of train, bus and car travellers in Norway. They were asked to choose between trip alternatives that were specified by: i) annual frequency of avalanches threatening the infrastructure; ii) average avalanche volume/width hitting the infrastructure; iii) annual no. of infrastructure closures; iv) the decennial no. of casualties for the specified travel mode; v) travel time; and vi) travel cost.The models of the choices show significantly negative coefficient signs for all six attributes. Thus, the travellers did on average indicate additional valuation of reducing avalanche frequency and avalanche volume/size, beyond the specified impacts on casualties and closures. When testing the valuation of avalanche frequency/size reduction against latent variables of avalanche insecurity and of neuroticism, using hybrid choice modelling, we find no significant associations. Insecurity/worry is not identified as a principal driver of the valuation of reduced avalanche risk, beyond the reduction in casualties and closures.